Formação stricto sensu dos professores da Rede Estadual Básica de Educação do Estado de Goiás – Sudoeste Goiano: evolução, tendências e perspectivas - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This work researches on the training of teachers of the Basic State Education Network of the State of Goiás - Southwest Goiano, focusing on teachers with stricto sensu postgraduate training (master's). The research's general objective is to analyze and discuss the training and research (dissertation) of teachers with a master's degree in the Basic State Education Network - Southwest Goiano. The methodology applied is of a qualitative approach and involved document analysis. For an in-depth analysis and discussion of the documents, the theoretical contribution of authors who write and discuss this theme was also used. The data collected and analyzed had as source the website of the Government Goiás 360°. Their classification was supported by documents from the Coordination for the Improvement of Higher Education Personnel - CAPES, National Association of Graduate Studies and Research in Education - ANPEd and Curriculum Lattes Platform. Documentary analysis shows that the implementation of graduate studies took place in a period when the government influenced this training model. This period between the 1960s and 1980s aimed to qualify teachers to work in Higher Education and train researchers who would contribute to the economic and social development of Brazil. It was found that the training of Basic Education teachers at the postgraduate level was only objectified at the end of the 20th century when the V and VI National Postgraduate Plan and the National Education Plans point out the need to qualify these teachers in order to improve the quality in the teaching level of Basic Education. Data analysis allows us to say that the change in the profile of teachers in the Southwest Goiano occurred as the public policies of the National Education Plan and the V and VI National Postgraduate Plan analyzed here were implemented, however with advances and setbacks, as, what was proposed was partially achieved.
Stricto sensu training of teachers of the Basic State Education Network of the State of Goiás - Southwest Goiás: evolution, trends and perspectives
Keywords: Educação Básica; Formação Stricto Sensu; Profissionalização; Sudoeste Goiano; Basic education; Stricto sensu formation; Professionalization; Southwest Goiás; CIENCIAS HUMANAS::EDUCACAO